Dynamics of arbuscular mycorrhizal fungal community structure and functioning along a nitrogen enrichment gradient in an alpine meadow ecosystem. Issue 4 (30th March 2018) - Jiang, Shengjing; Liu, Yongjun; Luo, Jiajia; Qin, Mingsen; Johnson, Nancy Collins; Öpik, Maarja; Vasar, Martti; Chai, Yuxing; Zhou, Xiaolong; Mao, Lin; Du, Guozhen; An, Lizhe; et al.
Summary: Nitrogen (N) availability is increasing dramatically in many ecosystems, but the influence of elevated N on the functioning of arbuscular mycorrhizal (AM) fungi in natural ecosystems is not well understood. We measured AM fungal community structure and mycorrhizal function simultaneously across an experimental N addition gradient in an alpine meadow that is limited by N but not by phosphorus (P). AM fungal communities at both whole‐plant‐community (mixed roots) and single‐plant‐species ( Elymus nutans roots) scales were described using pyro‐sequencing, and the mycorrhizal functioning was quantified using a mycorrhizal‐suppression treatment in the field (whole‐plant‐community scale) and a glasshouse inoculation experiment (single‐plant‐species scale). Nitrogen enrichment progressively reduced AM fungal abundance, changed AM fungal community composition, and shifted mycorrhizal functioning towards parasitism at both whole‐plant‐community and E. nutans scales. N‐induced shifts in AM fungal community composition were tightly linked to soil N availability and/or plant species richness, whereas the shifts in mycorrhizal function were associated with the communities of specific AM fungal lineages. The observed changes in both AM fungal community structure and functioning across an N enrichment gradient highlight that N enrichment of ecosystems that are not P‐limited can induce parasitic mycorrhizal functioning and influence plant community structure and ecosystem sustainability.